(untitled) - Lawrence Miall; Lawrence Miall; Mary Rudolf; Malcolm Levene (Oxford ; Malden, MA, 2003)
This popular title in the at a Glance series is structured into seven sections which reflect the full range of paediatrics and the real-life presentation of children. With new material on childhood obesity, allergy and living with chronic illness, Paediatrics at a Glance reflects the changing face of modern paediatrics and now features: Organisation by presenting symptom or problem, making the text highly relevant to clinical practice and problem-based learning Key points on history, examination and investigations listed with each presentation for rapid revision Expanded material on investigations, congenital abnormalities, newborn screening and immunisations Highly visual colour presentation and self-assessment case studies to make revision more rewarding Paediatrics at a Glance is an ideal companion for anyone about to start a paediatric attachment or module and will appeal to medical students, junior doctors and GP trainees. In addition, the text will provide valuable insight for nursing students, physiotherapists and other health professionals
Keywords: Pediatrics